Integrated Financial Management Assistance through E-DAMS Application Development at Mukhtar Syafa’at Blokagung Islamic Boarding School, Banyuwangi - Aula Izatul Aini; Komarudin A; Muhammad Imam Khaudli (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
This community service research focuses on addressing financial management challenges faced by PP Mukhtar Syafa'at, an Islamic boarding school in Banyuwangi. Established in 1990 with a substantial student population, the school grappled with manual financial recording, leading to errors, omissions, and decentralized contributions handling. This study employed Participatory Action Research (PAR) to implement an integrated financial management solution, introducing computerized recording and an accompanying application. As a result, the school transitioned from a manual to an integrated system, bolstered by computerized recording and a financial reporting application, enhancing administrative accountability and accuracy in financial reporting.